2015
DOI: 10.1149/2.0551507jes
|View full text |Cite
|
Sign up to set email alerts
|

Stability Investigation for Symmetric Solid Oxide Fuel Cell with La0.4Sr0.6Co0.2Fe0.7Nb0.1O3-δElectrode

Abstract: La 0.4 Sr 0.6 Co 0.2 Fe 0.7 Nb 0.1 O 3-δ (LSCFN) material has been prepared and evaluated as both cathode and anode for symmetric solid oxide fuel cell with La 0.8 Sr 0.2 Ga 0.83 Mg 0.17 O 3-δ electrolyte in this work. The stability of phase structure, electrode microstructure and polarization resistances for the LSCFN in the atmosphere of air and wet H 2 have been studied with time dependency by X-ray diffraction analysis, scanning electron microscope and electrochemical impedance spectroscopy. The maximum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…For STFN cell, the resistance did not vary significantly with p H2 and was as expected for the 0.3-mm-thick LSGM electrolyte, $0.21 U$cm 2 at 800 C. For STF, the observed increase in ohmic resistance is attributed to a contribution from the oxide anode, as discussed previously. 21 These results indicate that the conductivity of STFN was higher than that of STF; although it has previously been suggested that exsolved metallic particles contribute significantly to the anode conductivity, 35,43 it does not appear that the present particles are percolated (Figure 1). The high-frequency responses in Figure 5, which did not vary with p H 2 , can be attributed to the cathode.…”
Section: Electrochemical Performance Testmentioning
confidence: 68%
See 1 more Smart Citation
“…For STFN cell, the resistance did not vary significantly with p H2 and was as expected for the 0.3-mm-thick LSGM electrolyte, $0.21 U$cm 2 at 800 C. For STF, the observed increase in ohmic resistance is attributed to a contribution from the oxide anode, as discussed previously. 21 These results indicate that the conductivity of STFN was higher than that of STF; although it has previously been suggested that exsolved metallic particles contribute significantly to the anode conductivity, 35,43 it does not appear that the present particles are percolated (Figure 1). The high-frequency responses in Figure 5, which did not vary with p H 2 , can be attributed to the cathode.…”
Section: Electrochemical Performance Testmentioning
confidence: 68%
“…This method may have advantages compared with infiltration: (1) no extra process steps are required; (2) the catalyst particles can be substantially smaller and presumably more active than infiltrated particles 8,27,28 ; (3) the catalyst material can be introduced selectively into the anode functional layer; (4) it is possible to regenerate the nanoparticles via a redox cycle 29 ; and (5) the nanoparticles tend to be embedded into the oxide surface, which may discourage nanoparticle coarsening. 30 [32][33][34][35] Recent results indicate that the improved performance of La 0.8 Sr 0.2 Cr 0.82 Ru 0.18 O 3Àd anodes due to Ru nanoparticle formation can be quantitatively modeled by assuming that they accelerate the dissociative H 2 adsorption process. 21 Although most reports have featured tests with H 2 fuels, oxide anodes with exsolved metal nanoparticles have also been shown to provide good and stable performance with hydrocarbon fuels and to exhibit good tolerance to H 2 S contaminant.…”
Section: Context and Scalementioning
confidence: 99%
“…After being treated in H 2 , the LCFC was transformed into four different phases containing the CaO phase, La 2 O 3 phase, Co–Fe alloy phase, and LCFC perovskite. Different from other electrodes such as LSCFN, La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , and Pr 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , main structure of the LCFC perovskite phase still remained after being treated in the reduction atmosphere, which indicates the enhanced stability of the LCFC. From the reports in the literature, these newly formed three phases can exhibit specific functions when used as the fuel electrode in RSSOC.…”
Section: Resultsmentioning
confidence: 79%
“…The co-doping on B-site with reducible cations can enable exsolution of nanoparticles in a form of metallic alloys which gives an additional option to develop fuel electrode that are less prone to poisoning or carbon deposition issues. Fe, Co, Ni, Pd, and Ru were shown to exsolve from perovskite chromites or titanates perovskites [456][457][458][459] and can create alloys. The exsolution of Mn, Cr and/or NiO represent an attractive route to develop electrodes that are tolerant to carbon deposition for dry CO 2 electrolysis.…”
Section: Opportunitiesmentioning
confidence: 99%